IbM KELOMPOK PKK KELURAHAN BIRINGKASSI KECAMATAN BINAMU KABUPATEN JENEPONTO - Rahmawati, Rahmawati; Muflihunna, A.; Kamase, Jeni (Jurnal BALIRESO, 2018)
Dedication to the community is one manifestation of Tri darma college. IbM is done in KelurahanBiringkassi Binamu District Jeneponto Regency which aims to utilize the local produce ofcoconuts into high-value products of high economic value. IbM partners namely the PKK giventraining to produce traditional coconut oil, Virgin coconut oil (VCO) and nata de coco andproduction management and marketing. The results obtained are quite satisfactory, the partners arevery enthusiastic follow the activities of dedication and managed to make their own at home basedon the training materials that have been given.